2022
DOI: 10.1007/s10578-022-01420-w
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Socio-Emotional Disorders in Intellectual Giftedness: A Systematic Review

Abstract: This work systematically reviewed past literature to investigate the association between intellectual giftedness and socio-emotional and/or behavioral disorders. Nineteen studies met the inclusion criteria, 17 of which have children and/or adolescents as participants, and 12 have a non-gifted control group. Socio-emotional problems, such as withdrawal, were found in 3 out of 8 studies; internalizing disorders, such as anxiety, were found in 5 out of 9; externalizing disorders, such as hyperactivity, were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Studies have shown sex differences in peer problems and prosocial behavior and that girls generally exhibit higher levels of prosocial behavior and have better relationships with their peers than boys [55,56]. In this study, and consistent with the literature, prosocial behavior was higher in girls than boys.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown sex differences in peer problems and prosocial behavior and that girls generally exhibit higher levels of prosocial behavior and have better relationships with their peers than boys [55,56]. In this study, and consistent with the literature, prosocial behavior was higher in girls than boys.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the studies analyzed only the direct effects of PA on cognition, behavior, and motor skills, thus obtaining results that are probably biased. In addition, most of the studies carried out in the ASD population do not consider the other variables usually used in studies with a school-age population, such as BMI [58], commuting time to school [8], or the possible presence of the phenomenon of 'intellectual giftedness and ASD', which can be detected using systematic identification measures [59]. Because it is known that youth with ASD have lower levels of moderate PA during the school day and perform less daily PA than their typically developing peers [34], it would be interesting to know if the previous variables influence this population, in addition to other variables such as sleep quality and parental influence, in a similar way.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews have concluded that intellectually GC have similar or less psychopathology than their peers (Francis et al, 2016;Martin et al, 2009;Tourreix et al, 2023). However, Tasca et al (2022) posit that the evidence is insufficient to draw definitive conclusions. As all of these reviews included studies that used scales to compare psychopathology, they could not assess rates of psychiatric disorders, which is an important method of evaluating psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that GC may experience socioemotional difficulties. While some studies have found internalization problems such as anxiety, introversion, social withdrawal, low self-esteem, and extreme perfectionism to be associated with GC, others have also indicated a link between externalization problems, including emotional dysregulation, hyperactivity, irritability, and aggression (Tasca et al, 2022). A study assessing GC who sought treatment at a psychiatric clinic discovered that these children exhibited internalization problems, and those with advanced IQ scores displayed a higher frequency of behavioral problems (Guénolé et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation